2018
DOI: 10.1021/acs.jproteome.8b00528
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Response to Thaxtomin Phytotoxin Elicitor Cellobiose and to Deletion of Cellulose Utilization Regulator CebR in Streptomyces scabies

Abstract: Streptomyces scabies is responsible for common scab disease on root and tuber vegetables. Production of its main phytotoxin thaxtomin A is triggered upon transport of cellulose byproducts cellotriose and cellobiose, which disable the repression of the thaxtomin biosynthesis activator gene txtR by the cellulose utilization regulator CebR. To assess the intracellular response under conditions where S. scabies develops a virulent behavior, we performed a comparative proteomic analysis of wild-type S. scabies 87-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 83 publications
1
15
0
2
Order By: Relevance
“…Through our earlier proteomic analysis, we also observed that many proteins whose production was activated in S . scabiei 87-22 by cellobiose did not show production changes in the cebR null mutant (48). This could be explained by the possible ability of CebR to bind to “non- canonical” DNA sequences, as previously observed for other transcription factors that also link nutrient sensing and the specialized metabolism (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through our earlier proteomic analysis, we also observed that many proteins whose production was activated in S . scabiei 87-22 by cellobiose did not show production changes in the cebR null mutant (48). This could be explained by the possible ability of CebR to bind to “non- canonical” DNA sequences, as previously observed for other transcription factors that also link nutrient sensing and the specialized metabolism (50).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of CFA-Ile in our culture extracts indicates an important role for this molecule in the virulome, even though the addition of cello-oligosaccharides only has a limited positive impact on CFA-Ile production (Figure 1), while we observed massive overexpression via our transcriptomic analysis (Figure 2 and Table 2). Surprisingly, we previously reported in a proteomic study that the abundance of two proteins of the CFA-Ile biosynthetic pathway – SCAB79611 (Cfa2) and SCAB79671 (CFL) – significantly decreased upon cellobiose addition (48). Altogether, these results suggest that the production levels and the expression response of CFA-Ile biosynthetic proteins/genes are highly sensitive to the chosen culture conditions which could explain the important differences between our experimental setup conducted here in minimal media and earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…The entire regulation system of thaxtomin A production was then compared. No mutation predicted to impact the structure or the functionality of the proteins were found neither in the txtR gene directly involved in the transcriptional regulation of the other txt genes ( Joshi et al, 2007 ), the CebR cellulose utilization regulator, which is known to be the major regulator of virulence in S. scabies ( Planckaert et al, 2018 ), nor the CebEFG/MsiK transmembrane transporter involved in the internalization of cellobiose and cellotriose ( Jourdan et al, 2016 ). Moreover, homologs of all of these genes were found in S. acidiscabies LBUM 1476 suggesting that the differential production of thaxtomin A between the fourteen strains was not due to differential regulation by these systems.…”
Section: Discussionmentioning
confidence: 99%
“…A expressão do cluster genético da taxtomina é regulado pelo gene txtR, que pode ser ativado por celobiose (JIANG et al 2018), que não se limita apenas à produção de taxtomina A, mas também afeta a abundância de várias enzimas envolvidas na biossíntese de diferentes metabólitos secundários que podem estar envolvidos na virulência de S. scabiei (PLANCKAERT et al 2018). Embora a taxtomina A seja considerada a principal fitotoxina produzida por linhagens fitopatogênicas de Streptomyces, há Tabela 1.…”
Section: Patogenicidade De Streptomyces Sppunclassified
“…Onze tipos de taxtominas já foram isoladas a partir de linhagens de Streptomyces fitopatogênicas, e essas diferem apenas pela presença ou ausência de grupos hidroxila e N-metila em seus respectivos locais de substituição(KING et al 1989). As taxtominas são dipeptídeos cíclicos (2,5-dioxopiperazina) resultantes da condensação dos aminoácidos L-fenilalanina e os L-4-nitrotriptofano(WINN et al 2018;DUKE & DAYAN 2011;PLANCKAERT et al 2018). São consideradas como um composto estável que as bactérias excretam nos meios de cultivo em grandes quantidades(HILTUNEN et al 2011), sendo a taxtomina A considerada a principal fitotoxina entre as linhagens fitopatogênicas do gênero (CAO et al 2012; KING & CALHOUN 2009).…”
unclassified